Accounting Problems of Farming Activities - Pučinskas, Kazys (Ekonomika, 1997)
The latter article discusses accounting problems in the farming activities. Special attention is focused toward classification of production expenditures and accounting, calculation of production costs. It also indicates narrow specialization of Danish, Swedish, German farming, which conditions classification of production costs in the farming activities of the countries mentioned above.Multiple branching of the Lithuanian farming conditions in expenditure and cost calculations.The article discusses peculiarities of expenditure accounting created for the fanners’ personal matters as well as accounting experience compiled in the foreign countries is emphasizes.Moreover, the article presents proposals of perfection in the accounting of farming activities.